The short life cycle of Acutuncus antarcticus (Tardigrada) as adaptation to Antarctic environment - GIOVANNINI, ILARIA; REBECCHI, Lorena; GUIDETTI, Roberto; ALTIERO, Tiziana (Grifo, 2014)
The climate global change is altering the tropospheric ozone budget increasing harmful ultraviolet (UV) radiation with consequences on human and ecosystem health. Antarctic micrometazoans are particularly vulnerable to the synergic effects of increasing temperature and UV radiation as their growing season matches with the spring period of ozone depletion. The roles that phenotypic plasticity and genotypic evolution play in whether Antarctic organisms can cope with these environmental changes are not fully understood. Tardigrades represent one of the main terrestrial components of Antarctica fauna in terms of distribution, number of specimens and colonized substrates. Studies on adults of the eutardigrade Acutuncus antarcticus, one of the most abundant species in Antarctic bryophytes and freshwater sediments, showed that they survived to experimental exposition to increased temperature and UV radiation. These results suggest that A. antarcticus could survive to possible environmental changes. To test this hypothesis we firstly needed to know its life history traits, never studied before, in order to carry out further experiments on stress resistance of eggs and juveniles. Cultures were started using single specimens of A. antarcticus collected from a temporary freshwater pond at the Italian Antarctic base at Victoria Land. Animals were fed with the algae Chlorococcus sp., and reared at 14°C and 12h/12h L/D. A. antarcticus lays freely (rarely within exuvium) eggs hatching in 7-9 days. Newborns molt 2-3 times before their first oviposition that occurs at the age of 12-15 days. Successive ovipositions occur once a week (for 2-3 months) and are always preceded from a molting. The number of laid eggs (1-4 per oviposition) is a function of the female age. Throughout lifespan (3-4 months) each female lays up to 20 eggs. Individually reared newborns reached sexual maturity and, maintained isolated, laid eggs able to hatch. Males were never seen. Therefore this population reproduces via thelytokous parthenogenesis. The ...